Challenges of Caregivers Having Children with Autism in Kenya: Systematic Review - Brian Barasa Masaba; Jonathan Taiswa; Rose Maureen Mmusi-Phetoe (Wolters Kluwer Medknow Publications, 2021)
Background: Caring for children with Autism Spectrum Disorder (ASD) is demanding, especially where access to services and support are inadequate. The present study aimed to systematically review the challenges associated with the caregivers whose children have autism. Materials and Methods: A systematic review design was utilized. The searches were conducted from February 2019 to January 2020. A qualitative analysis that was based on meta-aggregation approach and thematic analysis was used. Thereafter, data was presented into themes. The quality of all included studies was assessed using the Critical Appraisal Skills Program (CASP). Results: The search generated 909 articles of which only 9 met the inclusion criteria. The main findings were discussed under the following three thematic domains: 1) Stigma, 2) Financial burden, and 3) Caregiving burden. Conclusions: Evidence from the data reviewed showed financial burden faced by the caregivers whose children are diagnosed with ASD. This was manifested through both direct and indirect cost of treatment. Another key finding was that majority of the caregivers faced stigma from the community. This implies the low level of awareness of the ASD within the community. The present study calls for more programs on the present research problem within the community so as to increase awareness. Furthermore, the current advocacy of Universal Health Coverage programs in the country should incorporate ASD children.